Rancang Bangun Antena Helix Mode Axial dan Patch Meanderline DGS untuk Aplikasi LPWAN Berbasis IoT pada Daerah Rural - Dodi Setiabudi; Lutfi Bayu Haniffian Wicaksono (Jurnal Rekayasa Elektrika, 2018)
Low Power Wide Area Networks (LPWAN) applications are a major concern in infrastructure. Rural are areas that have a poor quality signal; the cause lies in the location of the rural regions away from the coverage area Base Transceiver Station (BTS) so that the need for telecommunications equipment in the form of Global System for Mobile communications (GSM) repeaters. GSM repeater devices require an antenna that has a large gain mainly on the receiving antenna, one antenna that has a large gain character is helix axial mode has a large dimension resembling a spring and has a directional radiation pattern properties, whereas the antenna with an omnidirectional radiation pattern is a patch meander line antenna has compact dimensions and is easy to fabricate. The meanderline patch antenna has the disadvantage one of which is the small gain caused by trapped surface waves on the ground. This research will discuss the design and realisation of helix axial mode, and patch meanderline Defected Ground Structure (DGS) for Low Power Wide Area Networks (LPWAN) application in a rural area so it can be used for Internet of Things (IoT) based weather monitoring. Integrating antenna helix axial mode as receiving antenna and antenna patch meanderline DGS as rebroadcast antenna in GSM repeater able to make edge network in a rural area become High-Speed Packet Access + (HSPA +) network. The test result IoT based obtained the value of Received Signal Strength (RSSI) an average of -89 dBm in HSPA+ network.